Schiff Bases of Indoline-2,3-dione: Potential Novel Inhibitors of Mycobacterium Tuberculosis (Mtb) DNA Gyrase - Jane Thanassi (Molecules, 2011)
In the present study a series of Schiff bases of indoline-2,3-dione were synthesized and investigated for their Mtb gyrase inhibitory activity. Promising inhibitory activity was demonstrated with some of these derivatives, which exhibited IC50 values ranging from 50–157 mM. The orientation and the ligand-receptor interactions of such molecules within the Mtb DNA gyrase A subunit active site were investigated applying a multi-step docking protocol using Molecular Operating Environment (MOE) and Autodock4 docking software. The results revealed the importance of the isatin moiety and the connecting side chain for strong interactions with the enzyme active site. Among the tested compounds the terminal aromatic ring benzofuran showed the best activity. Promising new leads for developing a novel class of Mtb gyrase inhibitors were obtained from Schiff bases of indoline-2,3-dione.